Hipocresía y Voyerismo: El cuerpo desnudo y el sexo en Chile a fines del siglo XX y principios del siglo XXI. - ESTEFÓ CARRASCO, TOMÁS (Nomadías)
Fifty years after the coup d'état, its effects on Chilean society continue to be observed in political, economic, cultural and social aspects, but one area that has been less studied is its effect on the sexuality of Chilean society. A conservative dictatorship and a first decade of the transition to democracy with the Catholic Church as a moral compass, Chilean society seemed to confront itself through various discussions about the Body and Sex. Through the following article, four cases in which naked bodies have been exposed in public spaces or places of public access in the late twentieth century and early twenty-first century will be studied in order to understand and analyze the state of sexuality of the time and build a historical account of an area of society that in the last 30 years has undergone all kinds of changes.